Distribusi Kecepatan dan Konsentrasi Sedimen Suspensi pada Aliran Menikung (Studi Kasus pada Saluran Irigasi Mataram Yogyakarta) - Chairul Muharis - (Jurnal Ilmiah Poli Rekayasa, 2016)
The flow velocity and suspended sediment concentration are important parameters of sediment transport mechanisms, especially for agradation and degradation problems. The centrifugal force at the bend channels will increased flow velocity at the outer bank of the bend. It is of course also affects the distribution of flow velocity toward the outside and the inside of the bend channels. The change of the velocity distribution  it is very possible also changes the distribution of suspended sediment concentration. In this paper will discuss the velocity distribution profile and distribution of sediment concentration in the bend flow. This research was conducted at Mataram Irrigation Channel Yogyakarta. The channel rectangular in shape and made of masonry with angle bend 580. Measuring the flow velocity used Propeller currentmeter and  sediment concentration used Opcon Probe. Measuring flow velocity and sediment concentration conducted simultaneously for each measurement point.The results showed that due to the centrifugal force in bend flow, flow velocity distribution and sediment concentration distribution undergoing significant change the outside and the inside of the bend. In general, the distribution of flow velocity toward the outerbank of the bend has increased and the distribution suspended  sediment concentration has decrease  and the opposite occurs innerbank of the bend. A low velocity on the inner bank of the channel bend causes larger grains of sediment that settles and potentially silting.